Estudo de estabilidade e compatibilidade em formulações farmacêuticas contendo Ziprasidona ou Risperidona - Daniel, Josiane Souza Pereira (2013)
Stability studies of formulation containing the drugs risperidone or ziprasidone were done. These drugs were characterized through their physical and chemical characteristics by Differential Scanning Calorimetry (DSC), Thermogravimetry (TG), Spectroscopy Fourier Transform Infrared (FT-IR), X-ray Diffraction (PXRD), Scanning Electron Microscopy and Raman Spectroscopy (employed only for ziprasidone). Then, the drugs were submitted to stability studies using excipients, what is also called drug-excipient compatibility studies, according to the ICH standards (International Conference Harmonization), which provides international guidelines for its studies, adopted by ANVISA (National Agency for Sanitary Vigilance) in Brazil. Binary mixtures of each drug with excipient in a proportion of 1:1(w/w) immediately preparation and after stored instability chamber at 40°C±1°C and 75%± 5% of relative moisture. The samples were analyzed again after 3 and 6 months of incubation and the results compared with the initials. The techniques used for the risperidone study were DSC, TG, FT-IR associated with chemometric method Principal Component Analysis (PCA) and Liquid Chromatography (LC). For ziprasidone were used LC and FT-IR associated with PCA. Risperidone was characterized as a polymorphic form C by the PXRD. The DSC showed a melting endothermic event at the range of 170.5°C to 175.3°C and a melting enthalpy of ΔHf = 101.91 J g-1. Risperidone thermal degradation occurred on 230.3°C thus it was thermally stable at the range temperature employed in DSC analysis (30° to 200°C). The stability studies showed that risperidone was compatible with starch and sodium lauryl sulfate, whilst it showed chemical interaction with magnesium stearate, anhydrous lactose and microcrystalline cellulose. Ziprasidone was characterized by PXRD and FT-IR as the polymorphic form F. In despite of being crystalline it wasn’t possible to perform compatibility studies with DSC because this drug didn’t show a defined melting temperature in range it is thermally stable. The results of stability studies revealed an incompatibility with PVP and magnesium stearate.